2020
DOI: 10.3892/etm.2020.8465
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin promotes AMPK signaling to protect against high fat diet‑induced non‑alcoholic fatty liver in golden hamsters

Abstract: Non-alcoholic fatty liver disease (NAFLD) is characterized by diffuse fatty acid degeneration and excess fat accumulation in the liver. Notably, the currently available medications used to treat NAFLD remain limited. The aim of the present study was to investigate the protective role of atorvastatin (Ato) against NAFLD in golden hamsters fed a high fat diet (HFD) and in HepG2 cells treated with palmitate, and identify the underlying molecular mechanism. Ato (3 mg/kg) was administered orally every day for 8 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…Quantitative analysis showed that piperine at the concentrations of 50 or 100 μM markedly reduced the intracellular fat deposition by 36% (Figure C). The magnitude of piperine effect was similar to that induced by the positive control atorvastatin (10 μM), consistent with the report for reduction of the plasma levels of TC and LDL due to HMG-CoA reductase inhibition. , In addition, intracellular TG content was detected in HepG2 cells. As shown in Figure D, TG level was significantly increased upon FFA treatment.…”
Section: Resultssupporting
confidence: 89%
“…Quantitative analysis showed that piperine at the concentrations of 50 or 100 μM markedly reduced the intracellular fat deposition by 36% (Figure C). The magnitude of piperine effect was similar to that induced by the positive control atorvastatin (10 μM), consistent with the report for reduction of the plasma levels of TC and LDL due to HMG-CoA reductase inhibition. , In addition, intracellular TG content was detected in HepG2 cells. As shown in Figure D, TG level was significantly increased upon FFA treatment.…”
Section: Resultssupporting
confidence: 89%
“…In this study, both plasma concentrations of TG, LDL-cholesterol and HDL-cholesterol were increased in the NASH-fed hamster. While these observations are in agreement with other studies in high fat, high-fructose, high cholesterol diet-induced hamster models of dyslipidemia and hepatic steatosis [ 26 , 27 , 28 ], there are also studies showing no change in HDL-cholesterol in hamsters fed a diet containing fat, carbohydrates and cholesterol [ 29 , 30 ]. The dyslipidemia observed in human patients with NAFLD is typically characterized by increased plasma TG concentrations, increased or unchanged LDL-cholesterol and decreased HDL-cholesterol [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies in hamster models of NAFLD/NASH have reported that it is possible to induce most of the hallmarks of NASH in hamsters fed diets high in fat, with some combination of added carbohydrate and/or cholesterol during a shorter time span (12–25 weeks) [ 26 , 28 , 29 , 30 , 54 , 60 ]. In the study done by Briand and colleagues, hamsters were fed a free-choice diet (choice between chow and a high-fat diet (40.8 kcal% fat, 44.4 %kcal carbohydrate and 0.5% cholesterol) with 10% fructose in drinking water) for 12–25 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that atorvastatin significantly inhibited NAFLD progression via AMPK signaling pathway promotion in the golden hamster model of fat diet-NAFLD. In addition, they showed that AMPK inhibition by compound C counteracted the inhibitory effect of atorvastatin on fat accumulation in the HepG2 cell line [ 63 ]. In another study, Kim and colleagues who evaluated the effects of fluvastatin on cholesterol hemostasis regulation in the HepG2 cell line, demonstrated that fluvastatin induced AMPK and LKB phosphorylation and activation as a result of Sirtuin 6 activation with downstream phosphorylated sterol regulatory element binding protein‐1 that prevented lipid accumulation in hepatocytes [ 64 ].…”
Section: Ampk-associated Therapeutic Effects Of Statinsmentioning
confidence: 99%